2018
DOI: 10.1302/1863-2548.12.170192
|View full text |Cite
|
Sign up to set email alerts
|

Binary and analogue markers of skeletal maturity: Clinical utility of the thenar and plantar sesamoids

Abstract: PurposeWe investigate the thenar and plantar sesamoids as markers of skeletal maturity, and grade appearance using two scales, a binary system (absent or present), and an analogue system that relies upon judging regular changes in morphological appearance.MethodsWe studied 94 healthy children (49 female and 45 male patients) between ages three and 18 years who had approximately 700 serially acquired sets of radiographs and physical examinations. The children had at least annual radiographs taken of the left ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Systems that rely on analog markers of maturity, such as the GP Atlas and the Sanders Hand Classification, require clinicians to interpret morphologic changes at various ossification centers. 16 Given the subjectivity of these interpretations, prediction models relying on analog markers are prone to intraobserver and interobserver variability. [16][17][18] Cundy et al 17 examined the interpretation of 60 hand radiographs using the GP Atlas by 4 separate radiologists and found that half were assigned a skeletal age that differed by > 1 year and 10% varied by > 2 years between radiologists.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Systems that rely on analog markers of maturity, such as the GP Atlas and the Sanders Hand Classification, require clinicians to interpret morphologic changes at various ossification centers. 16 Given the subjectivity of these interpretations, prediction models relying on analog markers are prone to intraobserver and interobserver variability. [16][17][18] Cundy et al 17 examined the interpretation of 60 hand radiographs using the GP Atlas by 4 separate radiologists and found that half were assigned a skeletal age that differed by > 1 year and 10% varied by > 2 years between radiologists.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the objectivity in estimating bone age, other systems primarily utilize binary markers of osteologic maturity and assess whether a radiographic feature is present or absent. 16 The Shorthand Bone Age Assessment (SBA), for example, incorporates the presence of the hook of the hamate ossific nucleus, as well as the presence of the thumb sesamoid ossific nucleus, among other criteria to provide an estimate of bone age. 19 Given the more definitive nature of the skeletal assessment, systems utilizing binary markers have proven to have lower intraobserver and interobserver variability in comparison to systems composed primarily of analog markers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations